Students’ critical thinking across self-efficacy levels in STEM website-supported challenge-based differentiated learning - Fadhila Salvia Khairunnisa; Adi Satrio Ardiansyah; Rini Wulandari (Jurnal Elemen, 2026)
This study aims to examine the effectiveness of implementing Challenge-Based Differentiated Learning supported by a STEM website, analyze the influence of self-efficacy on critical thinking, and describe students’ critical thinking skills in relation to self-efficacy. The research employed a mixed-methods approach, a sequential explanatory design, and simple random sampling. Class VIII B served as the experimental group implementing the CB-DL model, and VIII A as the control group implementing problem-based learning, with each group consisting of 33 students. The results showed that the CB-DL model was effective in improving critical thinking skills, as indicated by an increase in the average pretest score from 65.15 to 83.33 on the posttest and a Cohen's D of 0.57. In addition, self-efficacy has a significant effect on critical thinking skills with a value R2 of 0.3542. Subjects with high self-efficacy met all six indicators of critical thinking skills, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. Those with moderate self-efficacy did not meet the self-regulation indicator, and those with low self-efficacy did not meet the explanation and self-regulation indicators. These findings confirm that the CB-DL supported by a STEM website, along with self-efficacy reinforcement, can optimize students’ critical thinking skills.